Conjugate natural convection in air filled tube inserted a square cavity - Öztop, Hakan Fehmi; Fu, Zaiguo; Yu, Bo; Wei, Jinjia (Pergamon-Elsevier Science Ltd, 2011)
Numerical analyses of fluid flow and heat transfer due to buoyancy forces in a tube inserted square cavity filled with fluid were carried out by using control volume method in this study. The cavity was heated from the left wall and cooled from the right isothermally and horizontal walls were adiabatic. A circular tube filled with air was inserted into the square cavity. The case that the inside and outside of the tube were filled with the same fluid (air) was examined. Varied solid materials were chosen as the tube wall. Results were obtained for different Rayleigh numbers (Ra = 10(4), 10(5) and 10(6)), thermal conductivity ratio of the fluid to the tube wall (k = 0.1, 1 and 10) and different location centers of the tube (c (0.25 <= x <= 0.75, 0.25 <= y <= 0.75)). Comparison with benchmark solutions of the natural convection in a cavity was performed and numerical results gave an acceptable agreement. It was found that varied location of the tube center can lead to different flow fields and heat transfer intensities which are also affected by the value of Rayleigh number. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Conjugate; Natural convection; Heat transfer; Inserted object; Annulus